Analysis of the Determinants of Purchasing Decisions for Traditional Herbal Medicine in Nguter District Sukoharjo Regency - Enggarbudi, Putri Arimbi; Mukson, Mukson; Prastiwi, Wahyu Dyah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Traditional herbal medicine is a product made from medicinal plants that are still very popular among the public. This study aimed to analyze the internal and external factors that influence consumer decisions in purchasing traditional herbal medicine products in Nguter District, Sukoharjo Regency. This research was conducted from January to March 2024. The research method used was the survey method. The research location was chosen purposively with the consideration that Nguter District is the center of traditional herbal medicine production. The sampling method used was accidental sampling. The sample size was determined using Purba's formula and 100 respondents were taken. The data collected consisted of primary data through interviews based on structured questionnaires and field observations, meanwhile secondary data were obtained from various relevant literature sources. The data analysis method was statistical analysis using logistic regression analysis. Hypotheses were tested with a significance level of 5%. The results showed that the factors of motivation, perception, attitude, product, price, place and promotion simultaneously have a significant effect on decisions to purchase traditional herbal medicine, while the factors that have a partially significant effect are attitude, product and place. This research was recommended to pay attention to internal and external factors to encourage consumer sustainability to utilize traditional herbal medicine, and the herbal medicine industry should pay attention to these factors.